Proceedings of the 23rd Conference on Computational Natural Language Learning (CoNLL) 2019
DOI: 10.18653/v1/k19-1082
|View full text |Cite
|
Sign up to set email alerts
|

Slang Detection and Identification

Abstract: The prevalence of informal language such as slang presents challenges for natural language systems, particularly in the automatic discovery of flexible word usages. Previous work has explored slang in terms of dictionary construction, sentiment analysis, word formation, and interpretation, but scarce research has attempted the basic problem of slang detection and identification. We examine the extent to which deep learning methods support automatic detection and identification of slang from natural sentences u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…In their study, both the spelling of a word and its context are provided as input to a translation model to decode a definition sentence. Pei et al (2019) proposed end-to-end neural models to detect and identify slang automatically in natural sentences. Kulkarni and Wang (2018) have proposed computational models that derive novel word forms of slang from spellings of existing words.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, both the spelling of a word and its context are provided as input to a translation model to decode a definition sentence. Pei et al (2019) proposed end-to-end neural models to detect and identify slang automatically in natural sentences. Kulkarni and Wang (2018) have proposed computational models that derive novel word forms of slang from spellings of existing words.…”
Section: Related Workmentioning
confidence: 99%
“…Here, we focus on syntax and linguistic context, although our framework should allow for the incorporation of social or extra-linguistic features as well. Recent work has found that the flexibility of slang is reflected prominently in syntactic shift (Pei et al, 2019). For example, ice-most commonly used as a noun-is used as a verb to express ''to kill'' (in Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Wikipedia) to transfer to another (e.g. social media) (Eisenstein, 2013b;Baldwin et al, 2013b;Belinkov and Bisk, 2018;Pei et al, 2019). Worse yet, for an overwhelming majority of lower resource languages, unstructured and unlabeled text on the Internet is often the sole source of data to train NLP systems (Joshi et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
“…Most of the dataset: formal-informal word pairs labeled with their word formation used to train these models are also in English. Other dictionaries of informal English words include SlangNet (Dhuliawala et al, 2016), SlangSD (Wu et al, 2018), and SLANGZY (Pei et al, 2019). There is also a dataset that contains pairs of formal-informal Indonesian words (Salsabila et al, 2018), but they are not annotated with word formation mechanisms.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation